2019
DOI: 10.1021/jacs.9b03361
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene-Selective Hydrogenation Catalyzed by Cationic Nickel Confined in Zeolite

Abstract: The selective hydrogenation of alkynes to alkenes is an important type of organic transformation with large-scale industrial applications. This transformation requires efficient catalysts with precise selectivity control, and palladium-based metallic catalysts are currently employed. Here we show that four-coordinated cationic nickel­(II) confined in zeolite can efficiently catalyze the selective hydrogenation of acetylene to ethylene, a key process for trace acetylene removal prior to the polymerization proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 54 publications
7
144
0
Order By: Relevance
“…[97] Furthermore, this result was verified from the XANES spectra of Zn-UiO-67-BPY ( Figure 13B), which showed the high oxidation state of Zn. Similarly, Chai et al [77] combined the information from Ni K-edge XANES and XPS measurements to confirm the presence of Ni 2+ in dehydrated Na-Ni@CHA. Another nonnoble metal-based SAC used in Figure 12.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…[97] Furthermore, this result was verified from the XANES spectra of Zn-UiO-67-BPY ( Figure 13B), which showed the high oxidation state of Zn. Similarly, Chai et al [77] combined the information from Ni K-edge XANES and XPS measurements to confirm the presence of Ni 2+ in dehydrated Na-Ni@CHA. Another nonnoble metal-based SAC used in Figure 12.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…XAS has also been widely used in the structural analysis of nonnoble metal SACs that are more easily incorporated into zeolites and MOFs. Chai et al [ 77 ] reported the synthesis of isolated Ni atomic sites confined within chabazite zeolite ( CHA ). By using the combination of XAS analysis and DFT calculations, the existence of single‐atom sites and the evolution of cationic nickel species confined within chabazite zeolite was revealed.…”
Section: Xas Analysis Of Sacs Supported By Crystalline Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supported Ni catalysts were applied to the selective hydrogenation of acetylene in the literature. Recently, Chai et al [20] reported that the cationic nickel confined in zeolite showed high ethylene selectivity and stability. Felix et al [21,22] synthesized a series of Ni-Zn alloy catalysts on the MgAl2O4 spinel support.…”
Section: Introductionmentioning
confidence: 99%
“…The semihydrogenation of acetylene was also performed on Ni@CHA, with CHA acting as an inorganic ligand for the Ni cationic complex and contributing to the heterolytic dissociation of H 2 . 60 Using Na-Ni@CHA as a catalyst, ethylene was produced in 97% yield. To understand this selectivity, the authors performed temperatureprogrammed desorption experiments (TPD), FTIR, DRIFT studies, and DFT calculations.…”
Section: Catalysis Science and Technologymentioning
confidence: 99%